2011
DOI: 10.1161/strokeaha.110.612937
|View full text |Cite
|
Sign up to set email alerts
|

Self-Reported Stroke Symptoms Without a Prior Diagnosis of Stroke or Transient Ischemic Attack

Abstract: Background and Purpose Previously in the REasons for Geographic And Racial Differences in Stroke (REGARDS) cohort, we found 18% of the stroke/TIA-free study population reported ≥ 1 stroke symptom (SS) at baseline. We sought to evaluate the additional impact of these stroke symptoms (SS) on risk for subsequent stroke. Methods REGARDS recruited 30,239 U.S. blacks and whites, aged 45+ in 2003–7, who are being followed every 6 months for events. All stroke events are physician-verified; those with prior diagnose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
61
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 33 publications
(65 citation statements)
references
References 30 publications
3
61
0
1
Order By: Relevance
“…Firstly, they add to evidence of the validity of self-reported stroke and hospital-coded stroke and their use in population health studies. Secondly, they confirm other evidence that a history of stroke may be used in a clinical context to inform patients' and physicians' decisions about secondary prevention [9,10,11,16,17]. Whether or not a history of stroke is confirmed by radiological imaging, the risk of incident stroke, vascular events and death is significantly increased in those who report or have a documented hospital diagnosis of history of a prior stroke event.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Firstly, they add to evidence of the validity of self-reported stroke and hospital-coded stroke and their use in population health studies. Secondly, they confirm other evidence that a history of stroke may be used in a clinical context to inform patients' and physicians' decisions about secondary prevention [9,10,11,16,17]. Whether or not a history of stroke is confirmed by radiological imaging, the risk of incident stroke, vascular events and death is significantly increased in those who report or have a documented hospital diagnosis of history of a prior stroke event.…”
Section: Discussionsupporting
confidence: 70%
“…The REasons for Geographic And Racial Differences in Stroke (REGARDS) study has reported that among participants without self-reported stroke or transient ischemic attack, prior stroke symptoms are highly predictive of future stroke events; almost as large as the impact of smoking and hypertension and larger than the impact of diabetes and heart disease [10]. The REGARDS study also suggests that there is a spectrum of risk from stroke symptoms (SS) only, to transient ischaemic attack (TIA), to distant stroke (DS), and recent stroke (RS) [11].…”
Section: Introductionmentioning
confidence: 99%
“…27 REGARDS and other studies are focusing efforts to advance the understanding of the potential role of each of these pathways – with very promising early findings to provide insights to target to reduce racial disparities. Examples of findings include: 1) documentation that blacks are actually more aware and more likely to be treated for hypertension, but that the treatment is much less likely to result in achieving blood pressure goals, 30 2) the potential that risk factors may in fact be have a differential impact in blacks and whites, with (for example) elevated levels of SBP being associated with approximately a three-fold larger increase risk of stroke in blacks than whites, 31 3) that after control for blood pressure levels, racial differences in duration of hypertension could be playing a substantial role in differential stroke risk, 31 and 4) numerous “novel” risk factors could be contributing to racial disparities in stroke incidence including disparities in the prevalence of stroke symptoms, 32 racial differences in awareness and treatment of atrial fibrillation, 33 racial differences in stroke severity arising from population stratification introduced through a genetic differences in hypertension or other risk factors, 34 differential impact of markers of inflammation including C-reactive protein (CRP), 35 racial differences in the age of menopause, 36 the role of diet, including differences in fish consumption, 37 and systemic infections such as tooth loss. 38 While much work remains, understanding these new pathways that potentially contribute to racial disparities in stroke incidence is a key first step to guiding the interventions to reduce this immense public health burden.…”
Section: Minority Health Research and Related Activitiesmentioning
confidence: 99%
“…Such symptoms may represent in part undiagnosed stroke/ transient ischemic attack, and the brief 6-question survey may be a remarkably cost-effective approach to detect a large portion of the population at high risk for incident stroke events. 18 Discontinuation of low-dose acetylsalicylic acid prescribed for secondary prevention increased the risk of stroke/transient ischemic attack by approximately 40% within the next 31 to 180 days in a case-control study nested within a UK primary care database. 19 In a population-based study (GCNKSS), 5.2% of strokes occurred within 60 days (most of them within 2 weeks) after stoppage of antithrombotic medication, mostly due to physician-initiated withdrawal in periprocedural periods.…”
Section: Stroke Symptoms and Stroke Therapy In Population Studiesmentioning
confidence: 99%
“…Риск инсульта независимо повышался на 21% для каждого из 6 приведенных симптомов. Эти симпто-мы могут быть проявлением недиагностированного инсульта/транзиторной ишемической атаки, а крат-кое анкетирование, состоящее из 6 вопросов, может оказаться экономически эффективным подходом для обнаружения большой доли лиц с высоким риском развития инсульта [18].…”
Section: симптомы инсульта и лечение инсульта в популяционных исследоunclassified